ANALISIS USAHA AGROINDUSTRI LEMANG DI KELURAHAN CINTA RAJA KECAMATAN SAIL KOTA PEKANBARU PROVINSI RIAU - Antonius F Tel; Sisca Vaulina (DINAMIKA PERTANIAN, 2024)
Lemang is a glutinous rice dish cooked in bamboo lined with banana leaves and roasted over an open fire. This study aims to analyze: 1) the characteristics of business actors and the profile of lemang businesses, 2) the procurement and use of raw materials, supporting materials, processing technology, production process, and labor in lemang businesses, 3) production costs, income, business efficiency, and added value, and 4) the marketing of lemang. This research uses a survey and census sampling technique involving 13 leading entrepreneurs from Cinta Raja Village, Sail District, Pekanbaru City. Data analysis was conducted using qualitative and quantitative descriptive methods. The findings show that most entrepreneurs are aged 47–53 (92.31%), have an average education of 9 years, and support 2–4 dependents (76.92%). The average business experience is 12.77 years. Lemang production reaches 24.62 kg per process at Rp 31,538.46/kg, generating a net income of Rp 276,043.84 per process with an RCR of 1.55. Lemang is marketed through three channels: directly to consumers, through retailers, or via collectors before reaching retailers and consumers.